GONZÁLEZ FERNÁNDEZ, Martín (2019). Michel de Montaigne (1533-1592): La filosofía como ensayo. (Defensa de los animales). Madrid: Sindéresis - González Jiménez-Peña, Alejandro (Daimon Revista Internacional de Filosofia, 2023)
Reseña de GONZÁLEZ FERNÁNDEZ, Martín (2019). Michel de Montaigne (1533-1592): La filosofía como ensayo. (Defensa de los animales). Madrid: Sindéresis